2018
DOI: 10.1038/s41598-018-24917-8
|View full text |Cite
|
Sign up to set email alerts
|

Low Bilirubin Levels Indicate a High Risk of Cerebral Deep White Matter Lesions in Apparently Healthy Subjects

Abstract: Recent studies have reported that deep white matter lesions (DWMLs) on magnetic resonance imaging scans are related to the risk of developing impaired cognitive function in future. Bilirubin exhibits a potent antioxidant effect and an inverse relationship has been reported between bilirubin levels and the risk of several atherosclerotic diseases; however, there is limited evidence with regard to the effect of bilirubin levels on cerebrovascular diseases including DWMLs. This cross-sectional study included 1121… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Padhraig Gormley 1-4,* , Verneri Anttila 2,3,5,* , Bendik S Winsvold [6][7][8] , Priit Palta 9 , Tonu Esko 2,10,11 , Tune H Pers 2,[11][12][13] , Kai-How Farh 2,5,14 , Ester Cuenca-Leon [1][2][3]15 , Mikko Muona 9,[16][17][18] , Nicholas A Furlotte 19 , Tobias Kurth 20,21 , Andres Ingason 22 , George McMahon 23 , Lannie Ligthart 24 , Gisela M Terwindt 25 , Mikko Kallela 26 , Tobias M Freilinger 27,28 , Caroline Ran 29 , Scott G Gordon 30 , Anine H Stam 25 , Stacy Steinberg 22 , Guntram Borck 31 , Markku Koiranen 32 , Lydia Quaye 33 , Hieab H H Adams 34,35 , Terho Lehtim€ aki 36 , Antti-Pekka Sarin 9 , Juho Wedenoja 37 , David A Hinds 19 , Julie E Buring 21,38…”
Section: Ihgc Members Contributing To the Gormley Et Al (2016) Migraine Gwasmentioning
confidence: 99%
See 1 more Smart Citation
“…Padhraig Gormley 1-4,* , Verneri Anttila 2,3,5,* , Bendik S Winsvold [6][7][8] , Priit Palta 9 , Tonu Esko 2,10,11 , Tune H Pers 2,[11][12][13] , Kai-How Farh 2,5,14 , Ester Cuenca-Leon [1][2][3]15 , Mikko Muona 9,[16][17][18] , Nicholas A Furlotte 19 , Tobias Kurth 20,21 , Andres Ingason 22 , George McMahon 23 , Lannie Ligthart 24 , Gisela M Terwindt 25 , Mikko Kallela 26 , Tobias M Freilinger 27,28 , Caroline Ran 29 , Scott G Gordon 30 , Anine H Stam 25 , Stacy Steinberg 22 , Guntram Borck 31 , Markku Koiranen 32 , Lydia Quaye 33 , Hieab H H Adams 34,35 , Terho Lehtim€ aki 36 , Antti-Pekka Sarin 9 , Juho Wedenoja 37 , David A Hinds 19 , Julie E Buring 21,38…”
Section: Ihgc Members Contributing To the Gormley Et Al (2016) Migraine Gwasmentioning
confidence: 99%
“…A low level of TB is not a concern for liver disorders, but it is associated with CVD risk factors (32) and stroke (33), which again supports higher risk of CVD among migraineurs. Interestingly, low TB levels are associated with higher risk of deep white matter lesions (34), which are more common among migraine patients (35). Clinically, increased serum level of GGT reflects liver dysfunction but epidemiologically it is associated with higher risk of CVD (36).…”
mentioning
confidence: 99%
“…Bilirubin has been shown to be protective against the development of ischemic damage associated with ischemic/reperfusion injury and endothelial activation (Yang et al, 2016). A recent cross-sectional study performed on 1121 healthy Japanese demonstrated that low levels of plasma bilirubin are associated with a high prevalence of ischemic modifications in brain white matter (Higuchi et al, 2018). In this context, a recent review form Thakkar et al (2019) rigorously analyzed clinical studies highlighting a relationship between bilirubin levels and cerebral ischemic stroke.…”
Section: Bilirubin and Ischemia/reperfusion Injurymentioning
confidence: 99%
“…IL-6), which are in turn responsible for CRP production in the liver tissue [11,12,28]. And other studies with different pathologies such as cardiovascular diseases [29], metabolic syndrome and type 2 diabetes [30], cerebrovascular diseases [31], osteoporosis [32], and even in rheumatoid osteoarthritis [33] also showed negative correlations with bilirubin concentrations. This has also been reported in studies evaluating the association between bilirubin and bacterial infections or associated models such as pathogen exposures including endotoxin, although not all studies show protective effects.…”
Section: Discussionmentioning
confidence: 93%